2005
DOI: 10.1007/s10800-005-9041-7
|View full text |Cite
|
Sign up to set email alerts
|

Continuous potentiometric monitoring of viagra (sildenafil) in pharmaceutical preparations using novel membrane sensors

Abstract: Two potentiometric sensors responsive to sildenafil citrate (SC) drug (the active component of viagra) are described, characterized, compared and used for drug assessment. The sensors are based on the use of the ion-association complexes of (SC) cation with tungstophosphate (TP) and reineckate (Re) anions as electroactive materials in plasticized poly(vinyl chloride) membranes. The sensors demonstrate fast near-Nernstian response for SC over the concentration ranges 1.0Â10 )2 -7.9Â10 )7 and 1.0Â10 )2 -1.0Â10 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The sildenafil-NaTPB and sildenafil-PMA complexes presented nernstian slopes of 55.5 and 53.5 mV per decade, over a sildenafil concentration range 10 À5 -10 À2 mol L À1 , with detection limits of 6 and 5 mmol L À1 , respectively, in pH 3-6 (Othman et al 2004). The TP and Re based membrane sensors presented a nernstian response for sildenafil in the concentration 7.9 Â 10 À7 À 1.0 Â 10 À2 mol L À1 and 1.0 Â 10 À6 À 1.0 Â 10 À2 mol L À1 , with slopes of 55.1-51.8 and 44.8-41.4 mV decade À1 , and detection limits of 0.53 and 0.67 mg L À1 , in pH 3-6, respectively (Hassan et al 2006). A membrane incorporating the sildenafil-TP complex in a tubular flow detector was adapted for flow injection analyses with a sampling frequency of 25-30 h À1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sildenafil-NaTPB and sildenafil-PMA complexes presented nernstian slopes of 55.5 and 53.5 mV per decade, over a sildenafil concentration range 10 À5 -10 À2 mol L À1 , with detection limits of 6 and 5 mmol L À1 , respectively, in pH 3-6 (Othman et al 2004). The TP and Re based membrane sensors presented a nernstian response for sildenafil in the concentration 7.9 Â 10 À7 À 1.0 Â 10 À2 mol L À1 and 1.0 Â 10 À6 À 1.0 Â 10 À2 mol L À1 , with slopes of 55.1-51.8 and 44.8-41.4 mV decade À1 , and detection limits of 0.53 and 0.67 mg L À1 , in pH 3-6, respectively (Hassan et al 2006). A membrane incorporating the sildenafil-TP complex in a tubular flow detector was adapted for flow injection analyses with a sampling frequency of 25-30 h À1 .…”
Section: Introductionmentioning
confidence: 99%
“…These methods, besides requiring low-cost apparatus, are highly sensitive and operationally simple. Poly(vinyl chloride) (PVC) matrix membrane sensors based on the use of ion association complexes of sildenafil with sodium tetraphenylborate (NaTPB) and phosphomolybdic acid (PMA) (Othman, Risk, and El-Shahawi 2004), reineckate (Re), and tungstophosphate (TP) (Hassan et al 2006) were reported as ion-selective electrodes for the potentiometric determination of sildenafil in pharmaceutical formulations. The sildenafil-NaTPB and sildenafil-PMA complexes presented nernstian slopes of 55.5 and 53.5 mV per decade, over a sildenafil concentration range 10 À5 -10 À2 mol L À1 , with detection limits of 6 and 5 mmol L À1 , respectively, in pH 3-6 (Othman et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Spectrofluorimetry and electroanalytical methods such as voltammetry using different electrodes were exploited by several researchers (Othman, Rizk, El-Shahawi, 2004;Hassan et al, 2006;Tyszczuk, Korolczuk, 2010;Wang et al, 2010;Balasoiu et al, 2011;Frag, Mohamed, Alelaiwe, 2011b;Wang, Gómez, Fernandez, 2013). However, these methods are laborious to be performed since they demand several types of reagents or sample treatment or involve many reactions steps and/or extraction processes for a quality control routine.…”
Section: Introductionmentioning
confidence: 99%
“…Such a membrane is usually prepared by incorporating an appropriate amounts of ion-pair and solvent mediator into a poly(viny1 chloride) (PVC) membrane matrix. The most widely used ion-pairing agents are tetraphenylborate derivatives [24,25], heteropoly compounds [26][27][28], miscellaneous salts and acids for cationic species [29] and quaternary ammonium [30] and phosphonium cations [31] for anionic species. A large number of ion selective electrodes based on ion pairs of various drug active compounds have been developed and reported in many papers [32][33][34][35] and several reviews [36][37].…”
Section: Introductionmentioning
confidence: 99%